Citation analysis of the highest-cited articles on developmental dysplasia of the hip. Issue 3 (May 2020) - Moscona, Leon; Castañeda, Pablo; Masrouha, Karim
Abstract : The purpose of this study is to determine the highest-cited articles on developmental dysplasia of the hip (DDH) and analyze their bibliometric characteristics. We searched the Web of Science (WoS) for articles with the highest number of citations on DDH and recorded their number of citations in WoS, Scopus, and Google Scholar (GS). We ranked and selected the top 100 cited articles. The average number of citations in WoS was 148 (range 66–638). The most-cited article in all databases was Crowe's total hip replacement cohort on DDH. The Journal of Bone and Joint Surgery American Volume (n = 35) had the most articles in the list, and the United States (n = 46) contributed with the most articles. The University of Bern had the most publications (n = 8). Most studies were therapeutic (n = 45) or diagnostic (n = 29). Hip preservation and arthroplasty investigations have had an increment in citations in recent decades. We provide an historical perspective on research conducted on DDH. A majority of the articles were observational and therapeutic. All databases had good correlation in the number of citations.